2019
DOI: 10.1007/s40273-019-00801-9
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Capacity Constraints in Economic Evaluations of Precision Medicine: A Systematic Review

Abstract: Background and Objective Precision (stratified or personalised) medicine is underpinned by the premise that it is feasible to identify known heterogeneity using a specific test or algorithm in patient populations and to use this information to guide patient care to improve health and well-being. This study aimed to understand if, and how, previous economic evaluations of precision medicine had taken account of the impact of capacity constraints. Methods A meta-review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
1
14
0
1
Order By: Relevance
“…These approaches could use static models with costs and benefits that are described as a function of implementation levels and producing estimates of cost-effectiveness at different levels or dynamic, multicohort models to capture the impact of changing marginal costs and benefits over time. 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches could use static models with costs and benefits that are described as a function of implementation levels and producing estimates of cost-effectiveness at different levels or dynamic, multicohort models to capture the impact of changing marginal costs and benefits over time. 18…”
Section: Discussionmentioning
confidence: 99%
“…A number of barriers (or capacity constraints) have been identified that may hinder fully comprehensive and inclusive access to the introduction of precision medicine: lack of sufficient laboratories to perform testing, logistical issues with coordinating testing and treatment, and sufficient numbers of trained laboratory staff, allied health care professionals, and clinicians. 1518 Concerns about the capacity of the National Health Service in England (NHS England) to provide the required EGFR mutation testing were raised during a NICE Technology Appraisal of gefitinib for non–small cell lung cancer. 19 Despite assurances at the time of the appraisal, subsequent evidence in 2014 suggested that only around 50% of eligible patients were receiving EGFR testing.…”
mentioning
confidence: 99%
“…The interview schedule was piloted with two clinicians before study recruitment began. The interview schedule for service providers (see extended data 25 ), and service commissioners (see extended data 26 ) were, informed by a systematic review of previous economic evaluations of precision medicine (including health technology assessments) 27 and consultation with two expert clinical advisors who are lung oncologists. The core questions for each of the two interview schedules were similar.…”
Section: Data Collectionmentioning
confidence: 99%
“…Aun cuando se han desarrollado esfuerzos menos sistematizados respecto a la utilización de las nuevas clasificaciones moleculares y su relación con nuevas drogas, este conocimiento generado, nos debe llamar a buscar el porcentaje de KRAS mutado en nuestros pacientes con CCR. Esto, no solo permitiría optimizar clínicamente la indica-ción de las drogas biológicas, sino que además, este paradigma de la medicina de precisión, permitiría realizar planificación sanitaria moderna, a partir de nuestra propia epidemiología molecular, lo que podría "teóricamente" tener un efecto fármaco-económico positivo, sin embargo, hacen falta más estudios para dilucidar este intrincado punto 49,50 .…”
Section: Conclusiones Y Desafíosunclassified